Injection molding advanced troubleshooting guide - Kerkstra, Randy; Brammer, Steve (Chemical engineer) (Hanser Publishers ; Hanser Publications, 2018)
This highly practical troubleshooting guide solves problems at the machine systematically and quickly. Drawing on a wealth of hands-on experience from the authors, who have built strong reputations in the field, the book is structured by type of problem/solution. Thus, it is an ideal reference to be consulted at the machine. Included is valuable information on robust process windows, cycle time evaluations, scrap savings, and runners/gates with no existing standard in the industry. No other book provides the unique insights found here--